2005
DOI: 10.1128/aac.49.6.2467-2473.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Confocal Microscopy To Analyze the Rate of Vancomycin Penetration through Staphylococcus aureus Biofilms

Abstract: When bacteria assume the biofilm mode of growth, they can tolerate levels of antimicrobial agents 10 to 1,000 times higher than the MICs of genetically equivalent planktonic bacteria. The properties of biofilms that give rise to antibiotic resistance are only partially understood. Inhibition of antibiotic penetration into the biofilm may play a role, but this has not been proven directly. In this report, penetration of the glycopeptide antibiotic vancomycin into viable Staphylococcus aureus biofilms was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
178
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(194 citation statements)
references
References 21 publications
10
178
1
2
Order By: Relevance
“…The penetration of antibiotics into biofilm is significantly reduced, and bacteria in the biofilm are exposed to the drug in gradually increasing doses. This gradual exposure can result in stress-induced metabolic or transcriptional changes in the bacteria and increased resistance to antibiotic therapy [30]. Some authors have reported multiple microbes in biofilms, and different biofilm species are associated with differences in disease severity and postoperative results [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The penetration of antibiotics into biofilm is significantly reduced, and bacteria in the biofilm are exposed to the drug in gradually increasing doses. This gradual exposure can result in stress-induced metabolic or transcriptional changes in the bacteria and increased resistance to antibiotic therapy [30]. Some authors have reported multiple microbes in biofilms, and different biofilm species are associated with differences in disease severity and postoperative results [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In studies using fluorescent dyes, diffusion was found to be the main mode of transport inside biofilm clusters. [115][116][117][118][119] Two important parameters in this respect are the particle size and the surface characteristics of the nanoparticles. Good penetration into biofilms is essential to deliver the antimicrobial agent to all bacterial cells inside the biofilm.…”
Section: Studying the Interaction And Transport Of Nanoparticles In Bmentioning
confidence: 99%
“…Jefferson et al (2005) showed that the antibiotic vancomycin can fully penetrate the biofilm but the diffusion rate in a biofilm is significantly reduced as compared to in water. This suggests that whereas planktonic bacteria are quickly exposed to a high concentration of antibiotics, bacteria in the deeper layers of the biofilm are exposed to a gradually increasing antibiotic concentration.…”
Section: Small-colony Variants (Scvs)mentioning
confidence: 99%